Framing Smart Nation: A moderated mediation analysis of frame-focus effects. Issue 9 (28th July 2020) - Mak, Joan Kai-Lin; Cho, Hichang
ABSTRACT: The rise of smart cities has emerged as a key policy thread that unites various government agencies in pursuit of a common objective: to become a digital city. However, these smart initiatives generate tradeoffs between economic growth and privacy concerns, with emphasis placed on data sharing for innovation, and surveillance for cybersecurity purposes. This study examines media framing in Singapore's Smart Nation initiatives. A between-subject experiment investigated the effect of news frames (gain versus loss) and regulatory focus (prevention versus promotion) on respondents' ( N = 157) opinions toward the Smart Nation. Gain frames were more effective when coupled with a promotion focus, and loss frames had a more impact when combined with a prevention focus. A moderated mediation analysis demonstrated support, attitudes, and perceived vulnerability mediated an interaction effect between gain/loss frames and regulatory focus, on the intention to participate in Smart Nation initiatives.